Anti‐sporulation effectiveness of leaf extracts of three Prosopis species on spoiling fungi collected from fresh produce in the Qatari market - Iman Saleh (14152878) (2023)
Fruit and vegetable post‐harvest infections are mainly caused by mycotoxin producing fungi. Post‐harvest diseases are causing food losses that lead to global economical problems. In this study, fresh samples of fruits and vegetables were collected from the local market for shelf‐life evaluation and identification of spoiling fungal types. Extracts of three locally available Prosopis species leaves were evaluated for their antifungal activity against the sporulation of the isolated fungi. Scanning electron microscopy was also used to evaluate spores and mycelium degenerative changes upon exposure to the leaves extracts. Out of the 156 samples tested, 88.5% showed fungal growth during the 17 days of the experiment. A total of 143 fungi were isolated and were subjected to microscopic identification. The fungal type that was most encountered was Aspergillus (30.1%). The fungal spoilage rate was significantly affected by the type of fresh produce (p ≤ 0.05), while collecting market and country of origin of the samples did not show a significant effect (p ≥ 0.05). Around 69.5% of the evaluated samples had a moderate to short shelf‐life. Ethanolic and aqueous extracts of the leaves of Prosopis juliflora, Prosopis cineraria and Prosopis farcta showed strong effectiveness against fungal sporulation when percent of germinated spores was calculated with alteration in spores and mycelium shapes under SEM. The most effective extract was the ethanolic leaves extract of P. juliflora. The three evaluated Prosopis spp. extracts showed variation in their effectiveness. A future combination of the most effective crude extracts could be used as a natural bio‐controller to replace commonly used chemical anti‐fungal agents. Other Information Published in: Food and Energy Security License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/fes3.461